"Плюси" та "мінуси" "принципів військової геометрії" Г.Боплана - Маслак, В.; Славко, О. (Спеціальні історичні дисципліни: питання теорії та методики, 2007)
На фоне развития математических знаний XVII в. анализируется учебник Г. Боплана по геометрии, написанный для использования в военном деле. The article shows “merits and demerits of G.Boplan’s «Military geometry principles” against a background of mathematical knowledge development of XVII century and analyses the course of geometry made for using it in military sciences.